Virtual employment — the form of future employment - I. V. Tsygankova (Омский научный вестник: Серия "Общество. История. Современность")
In his article « The future of work — flexibility and efficiency of virtual work» A. Ezer introduces the reader to virtual employment — one of the new forms that have emerged in the labor market due to digital technologies. Many of its conclusions, unfamiliar to a Russian reader, can be agreed, some require additional research and arguments. This article analyzes the main provisions made by A. Ezer, but presents the author’s point of view on the phenomena and processes in the labor market, which influenced the digitalization of the economy